Amination of ω‐Functionalized Aliphatic Primary Alcohols by a Biocatalytic Oxidation–Transamination Cascade. Issue 19 (3rd September 2015) - Pickl, Mathias; Fuchs, Michael; Glueck, Silvia M.; Faber, Kurt
Abstract Amination of non‐activated aliphatic fatty alcohols to the corresponding primary amines was achieved through a five‐enzyme cascade reaction by coupling a long‐chain alcohol oxidase from Aspergillus fumigatus (LCAO_Af) with a ω‐transaminase from Chromobacterium violaceum (ω‐TA_Cv). The alcohol was oxidized at the expense of molecular oxygen to yield the corresponding aldehyde, which was subsequently aminated by the PLP‐dependent ω‐TA to yield the final primary amine product. The overall cascade was optimized with respect to pH, O2 pressure, substrate concentration, decomposition of H2O2 (derived from alcohol oxidation), NADH regeneration, and biocatalyst ratio. The substrate scope of this concept was investigated under optimized conditions by using terminally functionalized C4–C11 fatty primary alcohols bearing halogen, alkyne, amino, hydroxy, thiol, and nitrile groups.